1984
DOI: 10.1099/00221287-130-1-119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endotoxin Treatment and Tumour Induction on Liver Catalase Activity in Mice

Abstract: Catalase activity in liver homogenates was studied in normal and low endotoxin (LPS)-responder mice treated with various doses of LPS from S. typhimurium B or bearing tumours induced by 3-methylcholanthrene. In normal LPS-responder (C3H/f) mice a dose of 40 micrograms LPS or tumour induction caused a reduction of catalase activity of about 50%. In low responder (C3H/HeJ) mice a reduction of the enzyme activity of over 40% was observed at a dose of 200 micrograms LPS. Tumour induction had no effect. In tumour-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The combined action of SOD, CAT, and GSH-Px serves as a potent antioxidant system, but the concentrations of SOD and CAT were not modified by any of the treatments (P > 0.05). Malondialdehyde is the most abundant reactive aldehyde resulting from lactoperoxidase activity and has been widely used as an index of oxidative deterioration of lipids in food and biological samples (Garcia-Castro and Gaya, 1984). In the current study, compared with the saline treatment (P < 0.05), we also found that LPS treatment led to a significantly greater level of MDA, but LPS + Arg treatment decreased that response.…”
Section: Resultssupporting
confidence: 62%
“…The combined action of SOD, CAT, and GSH-Px serves as a potent antioxidant system, but the concentrations of SOD and CAT were not modified by any of the treatments (P > 0.05). Malondialdehyde is the most abundant reactive aldehyde resulting from lactoperoxidase activity and has been widely used as an index of oxidative deterioration of lipids in food and biological samples (Garcia-Castro and Gaya, 1984). In the current study, compared with the saline treatment (P < 0.05), we also found that LPS treatment led to a significantly greater level of MDA, but LPS + Arg treatment decreased that response.…”
Section: Resultssupporting
confidence: 62%
“…Low-dose LPS administration caused significant decreases in kidney CAT mRNA, with no effect on CAT activity or mRNA in heart or liver. (38) A 40-mg LPS dose significantly reduced liver CAT activity in vivo 16 h after LPS administration, (39) and administration of 8 mg/kg LPS decreased CAT activity 24, 48, and 72 h after LPS administration. (3) Dhaunsi et al (40) suggested post-translational mechanisms of decreasing CAT activity by demonstrating increases in peroxisomal CAT protein with decreased CAT activity, in peroxisomes of liver homogenates after LPS administration.…”
Section: Discussionmentioning
confidence: 94%
“…Garcia-Castro and Gaya (1984); Spolarics et al (1996) and Spolarics and Wu (1997). The latter suggested that the recorded decrease in catalase activity may be due to enzyme inactivation by its own substrate.…”
Section: Discussionmentioning
confidence: 88%